Food-drug interaction as a risk factor of drug-induced diseases: epidemiology, risk factors, potential mechanisms of interaction - Pereverzev, A. P.; Ostroumova, O. D. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2021)
Any drug is potentially associated with the risk of adverse drug reactions (ADRs), the incidence of which in developed and developing countries is estimated at 6.3 (3.3—11.0) and 5.5 % (1.1—16.9), respectively. Many ADRs increase mortality and / or morbidity and / or cause clinical manifestations that require a patient to seek medical help or hospitalization; a special term has been introduced — drug-induced diseases. Food can interact with drugs and increase the risk of ADRs, including serious ones. The simultaneous intake of food and drugs can affect the bioavailability, pharmacokinetics, pharmacodynamics and therapeutic efficacy of drugs due to changes in drug absorption and metabolism. A striking example of the effect of food on the pharmacokinetic profile of drugs is the change in the bioavailability of the tyrosine kinase inhibitor lapatinib: compared with taking on an empty stomach, the bioavailability of lapatinib in a single dose of 1 500 mg after taking it together with high-calorie standard food increases by an average of 325 % — 4.25 times. In other words, the concentration of the drug in the blood serum after taking one tablet at the same time with food is comparable to taking 4 tablets on an empty stomach. Currently, there are no recommendations for choosing a dosage regimen for drugs depending on the qualitative and quantitative composition of food, as well as taking into account potential interactions with food components, although these recommendations are extremely necessary for patients and healthcare professionals. In this regard, this article summarizes the data available at the time of writing in open sources concerning the effect of food on the absorption and metabolism of drugs, and also describes the possible mechanisms of interaction.